Predation pressure by arthropods, birds, and rodents is interactively shaped by tree species richness, vegetation structure, and season - Anttonen, Perttu; Perles-Garcia, Maria; Kunz, Matthias; von Oheimb, Goddert; Li, Yi; Bruelheide, Helge; Ma, Ke-Ping; Zhu, Chao-Dong; Schuldt, Andreas (Frontiers in Ecology and Evolution, 2023)
Tree species richness, forest structure, and seasonal fluctuations between rainy and dry seasons can strongly affect trophic interactions in forest ecosystems, but the inter- and scale dependence of these variables remains unclear. Using artificial caterpillars (~18 000 replicates), we analyzed predation pressure by arthropods, birds and rodents along a tree species richness gradient across seasons in a subtropical tree diversity experiment (BEF-China). The aim of the study was to test if forest structure in addition to tree species richness has an effect on predation pressure, and to further specify which structural variables are important in driving predation. We assessed the effects of tree species richness and forest structure at plot and local neighborhood levels. We also included fine-scale placement covariates, plot size and topographical covariates of the study site. Forest structure and tree species richness independently and interactively affected predation pressure. Spatial scale was an important determinant for tree species richness and structural effects, extending from within plot scales to the overall heterogeneity of the plots’ surrounding environment. For example, the effect of branch density in the local neighborhood depended on both, surrounding tree species richness and plot level vegetation density. Similarly, visibility-enhancing factors increased attacks by arthropods (lack of branches in close surroundings) and by birds (open area) depending on the surrounding vegetation. Comparison of structural measures showed that predation pressure can be addressed in much higher detail with multiple specific structural features than with overall forest complexity. Seasonal change also affected predation pressure, with foliage being a stronger attractant in spring, but also by presumable topography driven study plot differences in sun exposure and humidity between rainy and dry season. Our study demonstrates that predation pressure is not simply a function of tree species richness or structure, but is shaped by the interplay of structural elements, spatial scale and seasonal dynamics along gradients of tree species richness and forest structure. The structural and seasonal effects are important to take into account when addressing how current and future biodiversity loss may change top-down control of herbivory and overall ecosystem functioning.